2015
DOI: 10.1007/s10826-015-0332-2
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizing and Measuring Safe, Stable, Nurturing Relationships and Environments in Educational Settings

Abstract: Most children and adolescents older than five years spend at least six hours of their day in school settings. Like parents, education professionals can promote health and protect youth from harm by providing safe, stable, nurturing relationships and environments. The Centers for Disease Control and Prevention (CDC) has developed a framework which posits that safe, stable, nurturing relationships and environments are Essentials for Childhood and are fundamental to promoting health and well-being; protecting you… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 91 publications
2
5
0
Order By: Relevance
“…This situation has been pointed out by teachers and school principals in Chile (López et al., ). These findings are consistent with international studies that indicate that there is a relationship between school violence and the community (Benbenishty & Astor, ; Chaux, ; Hernández de Frutos et al., ) and call for school‐community partnerships in which school and neighborhood safety be dealt with cooperatively and jointly (Robinson et al., ). These programs and interventions clearly call for school and community leaders to join forces and work together to improve both schools as well as community safety.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This situation has been pointed out by teachers and school principals in Chile (López et al., ). These findings are consistent with international studies that indicate that there is a relationship between school violence and the community (Benbenishty & Astor, ; Chaux, ; Hernández de Frutos et al., ) and call for school‐community partnerships in which school and neighborhood safety be dealt with cooperatively and jointly (Robinson et al., ). These programs and interventions clearly call for school and community leaders to join forces and work together to improve both schools as well as community safety.…”
Section: Discussionsupporting
confidence: 89%
“…Further, Flaspohler, Elfstrom, Vanderzee, Sink, and Birchmeier () found that students who are victims of school violence perceive their teachers as sources of support, more so than those who are aggressors. This is consistent with research findings that indicate that teachers are a source of primary support and act as primary agents and protective factors to whom students can reach out to when they are victims of violence at school (Humphrey & Symes, ; Robinson, Leeb, Merrick, & Forbes, ). Therefore, to parse out the associations between teacher victimization, peer victimization, and perceptions of school safety, the present study examines the predictive value of both victimization by teachers and other adults at school (negative valence) and of the social support provided by teachers to students (positive valence).…”
Section: School‐related Factors Involved In Perceived School Safetysupporting
confidence: 90%
“…." Under a list of qualities of the ideal school atmosphere, "the fair and consistent enforcement of rules and policies" nurturing relationships are included [83] (pp. 1496-1497).…”
Section: Teacher Hypocrisymentioning
confidence: 99%
“…These studies show connections between students’ emotional experiences at school and educational outcomes. Evidence also suggests that establishing safe and consistent relationships with adults is a valuable remedy for the challenges many youth face and that school staff beyond teachers can play a role as important adults in the lives of students (Chhuon & Wallace, 2014; Pittman et al, 2020; Robinson et al, 2016).…”
Section: Introductionmentioning
confidence: 99%